Estimate size sub-population by Killworth method - نايف, قنيبة نبيل; خلف, حسين حميد (Journal of Economics and Administrative Sciences, 2025)
The aim of the thesis is to estimate the partial and inaccessible population groups, which is a field study to estimate the number of drug’s users in the Baghdad governorate for males who are (15-60) years old.Because of the absence of data approved by government institutions, as well as the difficulty of estimating the numbers of these people from the traditional survey, in which the respondent expresses himself or his family members in some cases. In these challenges, the NSUM Network Scale-Up Method Is mainly based on asking respondents about the number of people they know in their network of drug addicts.Based on this principle, a statistical questionnaire was designed to include questions about population groups known to the number and other questions related to the target community, interviewed or interviewed by their parents at Ibn Rushd Hospital in Baghdad, with 104 persons for the period from April to June 2017.In order to extract the indicators, we was used network's package in R. First, the estimation of the personal network size is estimated by relying on the number known of 20 groups. In the Recursive Back estimation of these groups, the groups whose estimation is very remote The real value and here will be used 3 methods for the purpose of deleting the groups with weak estimates, namely the method of (direct deletion , trimming and successive) method have been found that there are 8 groups were underestimated and this means will be based on 12 groups to estimate the number of users and the number of (33,183) people, including (6,636) persons under the age of 18 years.